DETECTION OF ANTIBIOTIC RESIDUES IN MILK USING DELVOTEST KIT AND THE DISC ASSAY METHODS IN KHARTOUM STATE, SUDAN - M. Salman, Adil; A. ElNasri, Hind; A.M. Osman, Intisar (Journal of Veterinary Medicine and Animal Production, 2022)
Seven hundred thirty four stratified random raw milk samples were collected from forty seven dairyfarms and sale points, to detect antibiotic residues and to compare between the Delvotest kit and Disc assay methods. A direct interview (questionnaire) was used to collect data regarding the hygienic practices, management and antibiotic brands from dairy farms in Khartoum State. Mastitis and respiratory diseases were found in about 90% of the farms. The most frequent antibiotic used was Penicillin in 61.7% of the farms, while tetracycline was used in 27.7% of the farms. It was also found that antibiotic treated cows were milked together with the healthy ones. Eighty five percentof the farmers lacked the necessary information about antibiotic residues and appearance in food material, and the absence of veterinary supervision was observed in 72.3% of visited farms. From the total number of samples tested using Delvotest Kit, 33.1% of samples were positive, out of which 42.4% were from the farms milk while 23.2% were from sale points. Milk samples were also tested using the two tests, 12.8% of the samples were positive in both tests , while 75.1% were negative in both tests. When using the Kappa statistic the agreement between the two tests was 0.47 ( moderate agreement) and the percent aggrement was 78.3% . In conclusion,the study showedthat most farms are in moderate hygienic conditions with the frequent use of antibiotics and farmers lack the knowledge about the withdrawal period leading to the presence of the antibiotics in milk.